Translating Russian Folklore into Soviet Fantasy in Arkadi and Boris Strugatski's Monday Begins on Saturday and Catherynne M. Valente's Deathless. - MAGYARODY, KATHERINE (Marvels & Tales)
The article presents a literary criticism of the books "Monday Begins on Saturday: A Fairy Tale for Young Scientists" by Arkadi Strugatski and Boris Strugatski, and "Deathless" by Catherynne M. Valente. Topics discussed include the character of Koschei the Deathless in Russian folklore, the political use of the folklore by the Soviet Union, and the patriarchal Russian folk culture.